The Equine Flu in South America - F. Favaro, Patricia; J. Richtzenhain, Leonardo (Journal of Air and Water Borne Diseases, 2018)
This brief report summarizes equine influenza activity in South America, noting clinical presentation, transmission dynamics, and recent outbreaks. It reviews vaccination strategies, biosecurity measures, and surveillance needs for controlling spread. Practical guidance is provided for veterinarians and stable managers to reduce risk during regional circulation.
Keywords: Equine Influenza; South America; Vaccination; Biosecurity; Outbreaks